VD_FINDINFO AA 116/18 - 114/2019 vom 10. September 2019 - VD Tribunal cantonal (2019)
DEGRÉ DE L'INVALIDITÉ, RENTE D'INVALIDITÉ, AA, REVENU SANS INVALIDITÉ, GRATIFICATION | 18 al. 1 LAA, 19 LAA, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA